In vitro modeling of isoniazid resistance mechanisms in Mycobacterium tuberculosis H37Rv - Dokrungkoon, Thanadon; Tulyaprawat, Orawan; Suwannakarn, Kamol; Ngamskulrungroj, Popchai (Frontiers in Microbiology, 2023)
Mycobacterium tuberculosis (MTB), the causative agent of tuberculosis, has been a global threat to humans for several decades. Treatment of tuberculosis has become more difficult as the prevalence of drug-resistant tuberculosis has increased globally. To date, the detailed resistance mechanism is still unclear, especially the effect of anti-TB drug on MTB genome and the resistance mechanical events of MTB prior, during exposure to the drug, and finally becomes resistant. We used M. tuberculosis H37Rv as in vitro model for the generation of induced resistance by using a sub-inhibitory concentration of isoniazid and the generated resistance-associated variants (RAV) were identified by whole genome sequencing. The detection of an inhA promoter mutation (fabG1 -15C>T) which results in increased production of InhA protein was found to be a major mechanism for developing resistance to isoniazid in the first place. We observed adaptation of MTB resistance mechanisms in high isoniazid stress by alteration and abolishment of KatG due to the detection of katG S315N, the common region of mutation that confers isoniazid resistance, along with katG K414N, katG N138S, and katG A162E. Furthermore, we detected the ahpC -72C>T and ahpC 21C>A mutations, but further investigation is needed to determine their role in compensating for the loss of KatG activity. This suggests that increased InhA production is the main mechanism where there are low levels of isoniazid, whereas the alteration of KatG was found to be utilized in mycobacterium with high concentration of isoniazid. Our work demonstrates that this in vitro approach, the generation of induced resistance, could provide clinically relevant information after the fabG1 -15C>T mutation, the common mutation found in clinical isolates. Furthermore, other mutations detected in this work can be found in clinical isolates. These findings may shed light on the impact of isoniazid in the generation of RAV, as well as the resistance mechanism scenario that mycobacterium used under various isoniazid-pressuring conditions. More research is needed to better understand the role of RAV and resistance mechanical events within the mycobacterium genome in promoting a promising drug prediction platform that could lead to the right treatment for patients with MDR-TB and XDR-TB.